Data Mining Based on Neural Networks for Education Data Forecasting - Pabreja, Kavita (International Journal of Computer Sciences and Engineering, 2015)
Now-a-days, data mining has been used extensively in different domains of application for prediction. Data mining has demonstrated promising results in the field of educational prediction. Artificial Neural Networks in particular, find extensive application for understanding the peculiarities of education field but there is still a lot to be done as far as the Indian universities are concerned. In this paper, it has been verified that various personal and academic attributes of students can be used to predict the percentage of marks in graduation, using real data from the students of a Delhi state university’s affiliates.